2018
DOI: 10.1186/s40352-018-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal incarceration, child protection, and infant mortality: a descriptive study of infant children of women prisoners in Western Australia

Abstract: BackgroundThere are no population statistics collected on a routine basis on the children of prisoners in Australia. Accordingly, their potential vulnerability to adverse outcomes remains unclear. This study draws on linked administrative data to describe the exposure of children aged less than 2 years to maternal imprisonment in Western Australia, their contact with child protection services, and infant mortality rates.ResultsIn Western Australia, 36.5 per 1000 Indigenous (n = 804) and 1.3 per 1000 non-Indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…More than 80% of Aboriginal women in prison are mothers and many Aboriginal women also have primary caring responsibilities for children in their extended family (Bartels, 2012; Lawrie, 2003; Yeo, 2003). The incarceration of Aboriginal women causes IGT and disadvantage, including a current over-representation of Aboriginal children in out-of-home care (McMillen Dowell, Mejia, Preen, & Segal, 2018). The latter directly relates to the incarceration of Aboriginal mothers whose offending behavior itself is a response to personal, intergenerational, and cultural trauma (McCausland & Baldry, 2013; Segrave & Carlton, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of Aboriginal women in prison are mothers and many Aboriginal women also have primary caring responsibilities for children in their extended family (Bartels, 2012; Lawrie, 2003; Yeo, 2003). The incarceration of Aboriginal women causes IGT and disadvantage, including a current over-representation of Aboriginal children in out-of-home care (McMillen Dowell, Mejia, Preen, & Segal, 2018). The latter directly relates to the incarceration of Aboriginal mothers whose offending behavior itself is a response to personal, intergenerational, and cultural trauma (McCausland & Baldry, 2013; Segrave & Carlton, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that longer prison stays in pregnancy have been associated with higher birth weight ( Martin et al, 1997b , Howard et al, 2011 ). In our study of young Western Australian children whose mothers were imprisoned after birth and before their second birthday, we found nearly half of prison stays were for less than a fortnight and only one-fifth were for periods of six-months or more ( Dowell, Mejia, Preen, & Segal, 2018 ). In Western Australia, prisoners sentenced for periods less than six-months, in general, are not provided with a management plan or access to treatment programs ( Ferguson, 2015 ).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, given that about half of the women in prison are mothers,15 transition back to community for mothers with new infants may be different. This is a neglected but critically important area of public health research to prevent adverse health and social outcomes of maternal incarceration41 and intergenerational contact with the criminal justice system 42…”
Section: Discussionmentioning
confidence: 99%